2012
DOI: 10.1111/j.1540-8175.2012.01687.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Squatting Stress Echocardiography and Dobutamine Stress Echocardiography for the Diagnosis of Coronary Artery Disease

Abstract: These data indicate that squatting and dobutamine echocardiography are equally useful in the diagnosis of CAD. In selected patients, squatting echocardiography may be used in place of dobutamine echocardiography for the diagnosis of CAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 17 publications
0
5
0
4
Order By: Relevance
“…DSE has advantages over myocardial SPECT, including no irradiation, higher resolution, shorter test duration, immediate availability of results at the bedside, and the ability to perform stress and resting images in the same setting. Studies comparing DSE with coronary angiography have demonstrated relatively good sensitivity for ischemia with inducible WMA during DSE, ranging from 73% to 89% . Achieving the published levels of accuracy is not easy in daily clinical practice, however, because interpretation of DSE is often subjective and highly dependent on the operator's experience .…”
Section: Discussionmentioning
confidence: 99%
“…DSE has advantages over myocardial SPECT, including no irradiation, higher resolution, shorter test duration, immediate availability of results at the bedside, and the ability to perform stress and resting images in the same setting. Studies comparing DSE with coronary angiography have demonstrated relatively good sensitivity for ischemia with inducible WMA during DSE, ranging from 73% to 89% . Achieving the published levels of accuracy is not easy in daily clinical practice, however, because interpretation of DSE is often subjective and highly dependent on the operator's experience .…”
Section: Discussionmentioning
confidence: 99%
“…Безопасность и прогностическая ценность данной методики показаны в ряде исследований [9,10]. Chandraratna P.A et al отмечают, что чувстви-тельность стресс-ЭхоКГ в положении на корточках выше при многососудистом поражении и у больных с хорошо развитыми коллатералями [9].…”
Section: Discussionunclassified
“…Авторы показали, что приседание на корточки сопровождалось незначительным увеличением раз-меров полости ЛЖ в конце диастолы и систолы. ЧСС повышалась незначительно, но происходило значи-тельное увеличение цифр АД [9,10]. Другие исследо-ватели показали увеличение сердечного выброса и АД в сочетании с эффектом возрастания венозного возврата и сосудистого сопротивления, что способ-ствовало сдавлению вен и артерий.…”
Section: Discussionunclassified
See 2 more Smart Citations